Šiaurės žemaičių priebalsių audicinė (psichoakustinė) klasifikacija - Kliukienė, Regina (Kalbotyra, 1997)
The auditory hierarchical grouping of Žemaitian consonants has revealed two main types of consonant classes: a) fricative consonants + affricates; b) plosives + sonorants. The psychoacoustic analysis has revealed that: 1) the representatives of the dialect perceive affricates as the sounds similar to fricative consonants, although in the phonological system they should be considered as plosives; 2) plosives manifest greater similarity to sonorants; 3) the rolled sonorant r plays a special role in the consonant system; 4) vocal cords are of particular importance in the perception of consonants; 5) acoustic consonant classes in North Žemaitian do not actually differ from those in other dialects.